2015
DOI: 10.1111/ajt.13240
|View full text |Cite
|
Sign up to set email alerts
|

Severing Corneal Nerves in One Eye Induces Sympathetic Loss of Immune Privilege and Promotes Rejection of Future Corneal Allografts Placed in Either Eye

Abstract: Less than 10% of corneal allografts undergo rejection even though HLA matching is not performed. However, second corneal transplants experience a three-fold increase in rejection, which is not due to prior sensitization to histocompatibility antigens shared by the first and second transplants since corneal grafts are selected at random without histocompatibility matching. Using a mouse model of penetrating keratoplasty we found that 50% of the initial corneal transplants survived, yet 100% of the subsequent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 39 publications
4
71
2
Order By: Relevance
“…We concluded they were HSV-1 induced, as we never see sympathetic nerves in non-infected corneas [9, 10]. In other mouse models, it has been demonstrated that nerve damage alone is sufficient to increase inflammation in the cornea and rescind corneal immune privilege [42]. It remains to be determined whether these modest changes in corneal innervation and sensitivity following HSV-1 KOS infection of C57BL/6 mice result in, or contribute to, the subclinical inflammation that persists in the corneas remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded they were HSV-1 induced, as we never see sympathetic nerves in non-infected corneas [9, 10]. In other mouse models, it has been demonstrated that nerve damage alone is sufficient to increase inflammation in the cornea and rescind corneal immune privilege [42]. It remains to be determined whether these modest changes in corneal innervation and sensitivity following HSV-1 KOS infection of C57BL/6 mice result in, or contribute to, the subclinical inflammation that persists in the corneas remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we also report preservation of corneal nerve sensitivity in challenged mice. This novel insight is relevant as neurogenic maintenance of immune privilege has also been suggested (67,68). Further substantiating the interplay of vaccine-mediated correlates of protection and prevention of ocular disease will also provide a basis for the development of vaccines or therapies for use against other ocular pathogens.…”
Section: Discussionmentioning
confidence: 87%
“…10 We recently found that a similar condition occurs in a mouse model of penetrating keratoplasty in which 50% of the first-time corneal allografts enjoyed long-term survival even in the absence of major histocompatibility complex (MHC) matching and without immunosuppressive drugs. 11 However, >90% of subsequent corneal allografts underwent rejection even if the second corneal transplant was from a donor mouse strain entirely unrelated to the donor of the first corneal allograft. 11 The heightened incidence and tempo of rejection for second corneal allografts was associated with a loss of T reg function.…”
mentioning
confidence: 99%